Effective derivation of ventricular cardiomyocytes from hPSCs using ascorbic acid-containing maturation medium. Issue 1 (11th December 2023) - Kim, Ji-eun; Kim, Eun-Mi; Lee, Hyang-Ae; Kim, Ki-Suk
ABSTRACT: Cardiomyocytes derived from human pluripotent stem cells (hPSCs) can be used in various applications including disease modeling, drug safety screening, and novel cell-based cardiac therapies. Here, we report an optimized selection and maturation method to induce maturation of cardiomyocytes into a specific subtype after differentiation driven by the regulation of Wnt signaling. The medium used to optimize selection and maturation was in a glucose starvation conditions, supplemented with either a nutrition complex or ascorbic acid. Following optimized selection and maturation, more cardiac Troponin T (cTnT)-positive cardiomyocytes were detected using albumin and ascorbic acid than B27. In addition, ascorbic acid enriched maturation of ventricular cardiomyocytes. We compared cardiomyocyte-specific gene expression patterns under different selection and maturation conditions by next-generation sequencing (NGS) analysis. Our optimized conditions will enable simple and efficient maturation and specification of the desired cardiomyocyte subtype, facilitating both biomedical research and clinical applications.